Immunomagnetic Separation of Salmonella Typhimurium Based on Microfluidic Chip - JIN Yan, WANG Jingyi, CHENG Jianing, YU Lemin, ZHANG Bichen, ZHANG Yibo, XU Tongyu (Shipin Kexue)
This study developed an immunomagnetic separation microfluidic system for rapid isolation and enrichment of Salmonella typhimurium. The system consisted of a microfluidic chip, a microcontroller, and an electromagnetic separation and mixing module, which had the functions of electromagnetically driven mixing and magnetic separation. It enabled rapid incubation, isolation and enrichment of immunomagnetic beads with Salmonella typhimurium. Under the optimal conditions, the rapid capture and separation of Salmonella typhimurium in milk samples in the concentration range from 2 × 101 to 2 × 106 CFU/mL were achieved within 13 min, with capture rates between 33.3% and 67.5%. The limit of detection was 20 CFU/mL. This highly integrated immunomagnetic separation microfluidic system can enrich target bacteria from complex food matrices rapidly and accurately, thus providing an effective solution for the rapid detection of foodborne pathogenic bacteria, which is of great significance in addressing public health problems caused by foodborne diseases.